A compact and high sensitive photometer based on axial multi-reflection inside metal capillary: Application to detecting nitrite of nanomolar concentration. (November 2021) - Li, Xuejing; Huang, Hui; Cai, Weicheng; Bai, Min; Zhao, Jian; Liu, Pengbo; Sun, Changkai; Jin, Zengbin
Highlights: Axial back-and-forth-reflection (BFR) inside capillary was investigated. A photometer based on axial -BFR inside capillary was proposed. Optical-path enhancement of axial -BFR is more efficient than that of radial -BFR. In comparison with radial -BFR, axial -BFR features low transmission loss. The photometer features high sensitivity, compact, low cost and easy fabrication. Abstract: As for photometry analysis, increasing the optical-path (OP) via multi-reflection is an effective method for improving the detection sensitivity. In this paper, a photometer based on axial multi-reflection between two end-faces of capillary was proposed and investigated. The probe light can be back and forth reflected inside the capillary, by employing apertured silver-mirrors at both ends of a metal-capillary. With designed aperture profile (i.e., a central disc-aperture and a peripheral ring-aperture) of the mirror, a 4.2-fold enhancement on OP was realized (i.e., OP is 4.2 times the capillary length). Moreover, the photometer was applied to detecting nitrite with a detection limit of 1 nM, which exhibits 8.6 15 fold improvement compared with that of previous photometers with similar capillary length and the same chromogenic reagent without sample enrichment. The photometer features compact, low cost and easy fabrication.